Quelques réflexions sur BY en anglais - Anne-Marie Santin-Guettier (Anglophonia)
If we go back to the genesis of BY, we soon discover that it has the same roots as the preverb BE-. As a preposition, the major value of BY has always been «around». Our aim is not to label BY as a preposition, a particle or a postposition. By founding our study on examples, we shall try to find out the impact of the original value «around» on the semantic and syntactic uses of BY. Our hypothesis is that the spatial and temporal values of proximity and «passing through» are related to BY+Ving constructions and most structures with BY. Furthermore, the human mind tends to link two entities or two events if they stand in proximity to each other. BY lies at the core of this thesis. Lastly, the microsystem by which/whereby reveals that whereby plays a more complex grammatical role than by which.